2021
DOI: 10.1177/08862605211056032
|View full text |Cite
|
Sign up to set email alerts
|

Playing by the Rules? An Investigation of the Relationship Between Social Norms and Adolescents’ Hate Speech Perpetration in Schools

Abstract: Hate speech is often discussed and investigated as an online phenomenon, while hate speech among adolescents in the real world (e.g., in schools) has rarely been researched. Consequently, not much is known about potential interpersonal correlates and theoretical frameworks that might help us better understand why adolescents engage in hate speech in offline environments. To add to the literature, this study investigates hate speech perpetration among young people by utilizing the Social Cognitive Theory; more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…This result might also partially explain the initial research that revealed a negative association between a better school climate and less hate speech witnessing and victimization in schools ( Lehman, 2019 ). Furthermore, the present study extends previous research that has found that social norms within classrooms are related to adolescents’ engagement in hate speech as perpetrators ( Ballaschk et al, 2021 ; Wachs, Wettstein et al, 2022c , 2022d ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result might also partially explain the initial research that revealed a negative association between a better school climate and less hate speech witnessing and victimization in schools ( Lehman, 2019 ). Furthermore, the present study extends previous research that has found that social norms within classrooms are related to adolescents’ engagement in hate speech as perpetrators ( Ballaschk et al, 2021 ; Wachs, Wettstein et al, 2022c , 2022d ).…”
Section: Discussionsupporting
confidence: 88%
“…One study found that fair and transparent school rules are negatively linked to hate speech witnessing and victimization in schools ( Lehman, 2019 ). Other research documented that social norms within classrooms favoring hate speech are linked positively to adolescents’ hate speech perpetration ( Ballaschk et al, 2021 ; Wachs, Wettstein et al, 2022c , 2022d ). Adding to this line of research, the present study investigates whether classroom climate is positively related to counterspeech.…”
Section: A Socio-ecological Framework To Understand Counterspeech Amo...mentioning
confidence: 99%
“…According to this study, cyberhate perpetration can be understood as a possible reaction to feeling helpless concerning how to deal with cyberhate constructively. This assumption is further supported by current research with students showing that adolescents perpetrate hate speech (online and offline) to compensate for feelings of frustration and inferiority [ 16 , 70 ]. Our findings are in line with prior research that showed a positive relationship between non-productive coping and online or offline victimization [ 20 , 30 , 31 , 46 , 56 ], as well as online and offline perpetration [ 31 , 35 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 57%
“…The symbolic use of language differs along educational level with the use of swear words tending to be more common in lower-educated groups (e.g. Wachs et al, 2021). In the context of this study, however, education is a control variable, as the non-justification of norm violations and the use of insults are caused by common underlying third variables, such as social background.…”
Section: The Enforcement Of Social Norms In Online Protestsmentioning
confidence: 99%